Intervention programs on reading and writing processes in children with learning disorders: A review. - Villanueva-Bonilla, Cristian; Ríos-Gallardo, Ángela M. (Revista Mexicana de Neurociencia)
Reading comprehension is the goal of all reading and constitutes one of the fundamental axes of cognitive development in early childhood. The learning problems are manifested essentially in the school environment and significantly hinder academic activities that include reading and writing processes. This review identifies and compares published research on intervention processes in children with learning difficulties, specifically addressing dyslexia and dysgraphia. We selected eight studies in Spanish at a Latin American level and 23 studies in English at a global level. In conclusion, the current state of empirical research published in Spanish in intervention processes in children with learning difficulties is fewer in number in the past 10 years compared to literature in English, as evidenced by the search. The comparison established with literature published in English and worldwide indicates progressive advances of the Latin American literature in the subject addressed by this review, specifically in intervention programs focused on specific difficulties associated with learning disorders.